Geografia satirica dell’altro mondo: topoi, paradossi e obiettivi per un viaggio all’Ade (Ordia Prima, 2023)
Hades (or the afterlife) is a special place, far away, difficult to reach: it’s a different world, an upside down world. And it is a place of no return. It is the journey of the catabasis of heroes: Heracles, Theseus, Odysseus. In Lucian of Samosata it becomes –in the footsteps of Homeric myth and epic– a narrative paradigm and a way of satire. The new hero is Menippus in the Necromancy. The realm of the dead, with its special geography, is the place of otherness, i.e. the ideal place for satire to look at the reality of human life in a different way.